Mobilidade urbana sustentável: uma análise sobre o plano de mobilidade urbana da cidade de São Paulo - Schmal, Dominic (2018)
Cities and their policy makers face great pressure to address the current challenges of urban mobility. Rapid urbanization, population growth, demographic shifts and the scarcity of natural resources and climate change will continue to challenge cities around the world. Sustainable urban development is a global priority and is necessary. However most cities lack the capacity and resources to ensure development in a sustainable manner. Mobility is one of the most difficult issues to solve in large urban areas, involving public economic and socioenvironmental policy issues and depending on the technology and behavior of the population. Those cities that have decided to make daring moves to advance and diversify urban transport systems through a sustainable mobility plan can improve the attractiveness, productivity and quality of life of citizens. The great Brazilian metropolises must pay attention to the sustainable urban mobility initiatives in order to meet the trends of accelerated urbanization and the demographic changes that will occur in Brazil in the coming decades an in an exponential way. In this context, this paper seeks to answer the following question: How does São Paulo's mobility plan incorporate sustainable urban mobility principles? his analysis is carried out based on (i) the proposal of Subirats et al. (2008) for the constituent elements of a public policy and (ii) the Machado and Piccinini model (2018) related to the principles of sustainable urban mobility plans, comparing incorporation of such principles into the urban mobility plans of Barcelona and London. As a result of this analysis, the São Paulo Mobility Plan is considered to be advanced and equated in its quality in the structure of principles and elements of Sustainable Urban Mobility, when compared as urban mobility plans of international reference. However, the results also point to the need to evolve in themes not yet contemplated in the aforementioned plan and that have been gaining notoriety in other countries.